A new benchmark for machine learning applied to powder X-ray diffraction - Sergio Rincón; Gabriel González; Mario A. Macías; Pablo Arbeláez (Scientific Data)
Abstract Although crystal parameter prediction from powder X-ray diffraction has recently attracted the interest of the machine learning community, most existing datasets for this task are private and lack structural diversity. Here, we introduce the Simulated Powder X-ray Diffraction Open Database (SIMPOD), a new dataset that is public and structurally varied. This new benchmark includes 467,861 crystal structures from the Crystallography Open Database (COD) and their powder X-ray diffraction patterns. SIMPOD presents simulated one-dimensional powder X-ray diffractograms and derived two-dimensional radial images to facilitate the adoption of computer vision models for this task. We hope SIMPOD contributes to developing models that improve materials analysis from powder X-ray diffraction.